Mach-Zehnder interferometer implementation for thermo-optical and Kerr effect study - Bundulis, Arturs; Nitiss, Edgars; Busenbergs, Janis; Rutkis, Martins (Springer Verlag, 2018)
In this paper, we propose the Mach–Zehnder interferometric method for third-order nonlinear optical and thermo-optical studies. Both effects manifest themselves as refractive index dependence on the incident light intensity and are widely employed for multiple opto-optical and thermo-optical applications. With the implemented method, we have measured the Kerr and thermo-optical coefficients of chloroform under CW, ns and ps laser irradiance. The application of lasers with different light wavelengths, pulse duration and energy allowed us to distinguish the processes responsible for refractive index changes in the investigated solution. Presented setup was also used for demonstration of opto-optical switching. Results from Mach–Zehnder experiment were compared to Z-scan data obtained in our previous studies. Based on this, a quality comparison of both methods was assessed and advantages and disadvantages of each method were analyzed.
Scientific Research Project for Students and Young Researchers Nr. SJZ/2016/10; National Research Program “Multifunctional Materials and Composites, Photonics and Nanotechnology” (IMIS2) project “Photonics and materials for photonics”.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics